Antiviral Immunotoxin Against Bovine herpesvirus-1: Targeted Inhibition of Viral Replication and Apoptosis of Infected Cell - Xu, Jian; Li, Xiaoyang; Jiang, Bo; Feng, Xiaoyu; Wu, Jing; Cai, Yunhong; Zhang, Xixi; Huang, Xiufen; Sealy, Joshua E.; Iqbal, Munir; Li, Yongqing (Frontiers in Microbiology, 2018)
Bovine herpesvirus 1 (BoHV-1) is a highly contagious viral pathogen which causes infectious bovine rhinotracheitis in cattle worldwide. Currently, there is no antiviral prophylactic treatment available capable of mitigating the disease impact and facilitating recovery from latent infection. In this study, we have engineered a novel recombinant anti-BoHV-1 immunotoxin construct termed “BoScFv-PE38” that consists of a single-chain monoclonal antibody fragment (scFv) fused with an active domain of Pseudomonas exotoxin A as a toxic effector (PE38). The recombinant BoScFv-PE38 immunotoxin expressed in a prokaryotic expression system has specific binding affinity for BoHV-1 glycoprotein D (gD) with a dissociation constant (Kd) of 12.81 nM and for BoHV-1 virus particles with a Kd value of 97.63 nM. We demonstrate that the recombinant BoScFv-PE38 is internalized into MDBK cell compartments that inhibit BoHV-1 replication with a half-maximal inhibitory concentration (IC50) of 4.95±0.33 nM and a selective index (SI) of 456±31. Furthermore, the BoScFv-PE38 exerted a cytotoxic effect through the induction of ATP and ammonia, leading to apoptosis of BoHV-1-infected cells and the inhibition of BoHV-1 replication in MDBK cells. Collectively, we show that BoScFv-PE38 can potentially be employed as a therapeutic agent for the treatment of BoHV-1 infection.